Design of Real Time Anemometer Based on Wind Speed-Direction and Temperature - Triwahju Hardianto; Bambang Supeno; Dedy Kurnia Setiawan; Gunawan Gunawan (Institute of Advanced Engineering and Science, 2017)
Data acquisition of wind speed, wind direction and environmental temperature are needed to get the data potential of wind power. The aim of this research is to generate a device of wind speed, wind direction and temperature with the real time condition. With this device, we will obtain an analysis about the potential of wind power electrical generation around the Puger beach, Jember, Indonesia. In this study, parameters investigated were made into three types of measurement variables that measure of wind speed, wind direction, temperature and a data to show real time data..The device which is used to measure wind speed using hall effect sensor as a transducer. With using of the active magnet that spins will be created pwm that will be read by sensor to get the wind speed. As for the shows wind direction, we use a compass sensor CMPS 03 is a digital sensor that outputs in the form of digital bits so that be able to show wind direction from 0° to 360°. The magnitude of angle will be used in analyzing the direction of the wind, the real time clock (RTC) will be used to directly to determine the time and date of recording data. Then the temperature DS1621 sensor to show environmental temperature.